Determination of nutrient adequacy of the food catered in the child care homes (CCHs) of Sunsari district. (February 2019) - Sah, Om Prakash; Vyas, Pallavi; Shrestha, Dinesh
Summary: Malnutrition continues to be a primary cause of ill health and mortality among school age orphan and vulnerable children in developing countries. Objective: Determination of nutrient adequacy of the food catered in the child care homes of Sunsari district. Methods: Weighing method was used for determining the amount of food eaten. T-test and bivariate spearman correlation coefficients were used to compare the nutrient intake with respective RDA and to determine the association between nutrient intake and malnutrition respectively. Results: The study revealed, 33.82% and 17.39% of study population were stunted and underweight respectively. Equal percentages (7.81%) of study population were overweight and thin. Probability of calorie and protein adequacy was found in 52.94% and 89.71% of study population in CCHs. Calcium intake of all children and adolescent were found to be below their RDA. Cereals contributed the highest amount by weight (355.3 g) and proportion (39%) to the total diet for the study population in CCHs. Fruits 1% (12.9 g) and additional oil 2% (20.9 g) made a small contribution to the study population dietary intake. Fish and eggs were completely lacking in their diet. Probability of iron inadequacy was found in 80.9% of study population in CCHs.